From Electronic to Mobile Government - Homburg, Vincent; Lampoltshammer, Thomas J; Solvak, Mihkel (Springer Nature, 2025)
The open access book combines insights from policy sciences (backgrounds of cross-border coordination challenges), design science (development of architectures for mobile services), information ethics (privacy and security of e-government services in international arenas) and business studies (changes in existing business models). The notably interdisciplinary character provides scholars and policy professionals working in specific (legal, political, engineering) disciplines a unique outlook on how policy making, implementation, and pilots are related in multi-level and cross-border governance. The book presents the results of the EU-funded “Mobile Cross-Border Government Services for Europe” (mGov4EU) project in which various pilots implemented and validated enhanced infrastructure services for electronic voting, smart mobility, and mobile signing. Together, the single pilots demonstrated how enhanced electronic identities and trust services (eIDAS) and Single Digital Gateway Regulation (SDGR) layers can accommodate once-only, digital-by-default and mobile-first principles. By taking advantage of security features of modern smartphones like hardware-backed secure elements together with integrated convenience elements like biometric sensors, this research showed how both the security needs and data-protection expectations one has into public services and the usability challenges that arise when accessing complex services using constrained mobile devices meet. This book is the first one in his kind to address this gap in the academic knowledge, as well as this gap in available compendiums for policy professionals at European levels of decision-making, as well as for policymakers and experts working on electronic identification, cross-border and cross-sector information exchange in the various member states of the European Union. This way, it serves various audiences: first, researchers in informatics-related areas like information systems, electronic government, and mobile applications, as it describes empirical examples of secure, easy-to-use and cross-border electronic services that have been developed and successfully tested in practice. Second, it also caters to researchers in international relations or political science as well as policymakers and politicians, both at national or European levels, who are involved in drafting policies and implementing European initiatives in relation to the building blocks of next-generation e-government services.